In praise of fractionated trading zones: Respectful partnerships in management innovation - Pandza, K; Whittington, R; Hautz, J (Now Publishers, 2022)
We address the contemporary challenge of increasing the rate of management innovation by asserting the value of ‘fractionated trading zones’. By contrast with the homogenization of academia, business and consulting proposed by some scholars concerned for management innovation, fractionated trading zones involve partnerships that are respectful of the distinct characters of the various communities. We demonstrate the potential of such fractionated trading zones by examining the diverse contributors to three management innovations in strategy: portfolio models, value innovation and participative strategizing. Each of these innovations was brought about by respectful partnerships between academia, business and consulting, facilitated by the development of visual or metaphorical boundary objects and the interventions of transcendent interactional experts. We conclude by recommending policies for both academics and practitioners in order to promote the creation of innovativepartnerships across the divide.